CONSUMER SHADOW BANKS - Phillips, Todd; Bruckner, Matthew Adam (Stanford law & policy review, 2024)
There is no risk-free way to engage in bank-like activities. Entities that take deposits, transmit money, or otherwise provide custody of funds all generally engage in maturity transformation, a process that turns short-term debts into longer-term investments. Maturity transformation is inherently dangerous. Firms that engage in these activities also face moral hazard, whereby they may act contrary to their customers' interests. Without government intervention and a backstop, institutions that engage in these activities are liable to run, harming their customers. For that reason, the government heavily regulates bank, serves as their lender of last resort, and provides their depositors with insurance. Scholars have long been wary of "shadow banks:" nonbanks that perform bank-like activities without the guardrails that protect bank depositors.